2006
DOI: 10.1354/vp.43-5-740
|View full text |Cite
|
Sign up to set email alerts
|

Age-related and Non-age—related Changes in 100 Surveyed Horse Brains

Abstract: Brains from 100 horses, aged 2-25 years, were systematically examined by histopathology at 46 different neuroanatomical sites. The horses were sourced from a slaughterhouse (group A, n = 57), from a kennel that collected dead animals, and from 2 diagnostic laboratories (group B, n = 43). All horses from group A and 26 horses from group B were examined by a veterinarian in the period before death. None of the horses were known to exhibit clinical signs suggestive of neurologic disease. Among the main changes id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
29
5
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 25 publications
6
29
5
2
Order By: Relevance
“…Furthermore, an extraordinary amount of empty Schwann cells (after degeneration of the axons) was found in in elderly people (Ochoa andMair 1969, Toghi et al 1977). These findings from human medicine are not in accordance with a study performed by Jahns et al (2006), where age-dependent changes found in brain tissue of 100 horses were not consistent with degeneration. The changes in this study consisted of intra-neuronal (n=97), glial or extracellular lipofuscin (n=41), calcium deposits (n=24) and hemosiderin deposits around blood vessels (n=60).…”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…Furthermore, an extraordinary amount of empty Schwann cells (after degeneration of the axons) was found in in elderly people (Ochoa andMair 1969, Toghi et al 1977). These findings from human medicine are not in accordance with a study performed by Jahns et al (2006), where age-dependent changes found in brain tissue of 100 horses were not consistent with degeneration. The changes in this study consisted of intra-neuronal (n=97), glial or extracellular lipofuscin (n=41), calcium deposits (n=24) and hemosiderin deposits around blood vessels (n=60).…”
Section: Discussioncontrasting
confidence: 97%
“…The changes in this study consisted of intra-neuronal (n=97), glial or extracellular lipofuscin (n=41), calcium deposits (n=24) and hemosiderin deposits around blood vessels (n=60). In two horses, Alzheimer Type II cells were found (Jahns et al 2006). These changes could not be retraced in our study.…”
Section: Discussioncontrasting
confidence: 76%
“…In this study, macroscopically and microscopically ventricular dilatation and ependymal undulation with inflammation were noted; these results were previously reported in other animal species [8,10] but not in horses. Histopathological findings in the aging brains in horses were similar with earlier studies done with horses [11,13,14,23] , other animal species [8,10,21,22,24] and people [4,25,26] . In the study, even though no sex or breed difference was found, significant difference was found with aging.…”
Section: Discussionsupporting
confidence: 87%
“…Neuroaxonal dystrophy, calcification and inflammation are the common changes in the aging brains, pathogenesis and functional consequences of these changes are not fully understood [11][12][13][14] . Lipofuscin and hemosiderin pigments, calcium deposits, satellitosis [11] neuroaxonal dystrophy, cerebrovascular disease [13,14] and Alzheimer type II cells were reported in previous studies [13] in the elderly horse brains. Furthermore, changes in the aging brain were demonstrated by some markers.…”
Section: Introductionmentioning
confidence: 99%
“…Essas lesões também foram descritas em casos de intoxicação espontânea e experimental por S. paniculatum (Guaraná et al 2011) e por S. fastigiatum (Riet-Correa et al 1983, Rech et al 2006. A presença de esferóides axonais no tronco encefálico de equinos e degerenação Walleriana na substância branca da medula espinhal de ovinos e caprinos são considerados achados incidentais (Hooper 1999, Jahns et al 2006.…”
Section: Discussionunclassified